Heterostructure molybdenum disulfide / black titanium material, preparation method and use thereof
Patent Information
- Application Number
- CN202410478342.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-19
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-04-19
AI Technical Summary
对于正极材料的设计,一般是与物理阻隔、化学吸附相结合,但是随着反应的不断进行,中间产物多硫化锂的不断积累,现有方法达到的效果并不显著,寻求一种切实有效的光催化剂作为正极材料来促进多硫化物的快速转化显得至关重要
[0020]根据本发明,与现有技术相比,优异效果在于:是使用硼氢化钠还原得到黑钛的方法,此方法工艺安全、简单且成本低廉;同时由于硼氢化钠的强还原作用,使得二硫化钼/黑钛材料中具有氧空位和低价钛,引入了缺陷工程,可以提高光催化活性和光降解抗性。另外,所制备的二硫化钼/黑钛材料具有独特的异质结构,从而具有更靠近锂硫电池充放电电压窗口的价带和导带以及更窄的带隙而具有更好的太阳光吸收与光生载流子分离能力,进而极大地改善光增益锂硫电池的比容量性能和循环稳定性能;同时该材料由于黑钛的存在,电导率得到了极大地提高并优于现在的大多数锂硫电池的正极材料。
Smart Images

Figure CN118373452B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to inorganic chemistry technology, and more particularly to a heterostructured molybdenum disulfide / black titanium material, its preparation method, and its applications. Background Technology
[0002] Growing energy demands and environmental awareness are accelerating the shift from traditional fossil fuels to clean and renewable energy, particularly electricity. Future applications, such as portable electronic devices, electric vehicles, and interstellar travel, are also placing higher demands on power supply systems. These increasing demands make the mission of designing new high-energy-density batteries more urgent than ever before. Lithium-ion batteries (LIBs) have dominated the rechargeable battery market since their commercialization in the late 1990s and are gradually permeating all aspects of our daily lives. Currently, lithium-ion batteries are approaching their theoretical specific energy (387Wh / kg). -1 In the long run, despite extensive optimization, the inherent limitations of lithium-ion battery chemistry will still not meet the demands for higher energy densities. This has therefore spurred a series of in-depth research activities on alternative next-generation energy storage devices.
[0003] Lithium-sulfur batteries offer a capacity of 2600 Wh / kg due to the multi-electron electrochemical reaction between the sulfur cathode and lithium anode. -1 Its theoretical energy density is five times that of traditional lithium-ion batteries. Furthermore, sulfur, as a cathode material, has advantages such as being naturally abundant, inexpensive, and environmentally friendly. Therefore, lithium-sulfur batteries are considered one of the most advanced energy storage devices capable of meeting the needs of a constantly evolving market.
[0004] Sulfur cathodes are a key component of lithium-sulfur batteries, contributing to their high energy density. However, this component also presents serious problems. Sulfur has poor electrochemical properties, making it unsuitable for direct use as a cathode material in lithium-sulfur batteries. Therefore, designing a suitable cathode material for lithium-sulfur batteries is crucial for suppressing the shuttle effect and improving electrochemical performance. Cathode material design typically combines physical barriers and chemical adsorption; however, as the reaction progresses and intermediate lithium polysulfides accumulate, existing methods are not very effective. Therefore, finding a practical and effective photocatalyst as a cathode material to promote the rapid conversion of polysulfides is essential. Summary of the Invention
[0005] In view of this, the purpose of the present invention is to provide a heterostructured molybdenum disulfide / black titanium material, its preparation method, and its uses.
[0006] According to a first aspect of the present invention, a method for preparing a heterostructured molybdenum disulfide / black titanium material is provided, comprising: synthesizing an intermediate product, a titanium dioxide precursor, using a titanium source, acetic acid, oxalic acid, and water and ethanol solvents as raw materials; reducing the titanium dioxide precursor at high temperature with sodium borohydride; and obtaining the heterostructured molybdenum disulfide / black titanium material by a hydrothermal method under the synergistic effect of thioacetamide, sodium molybdate dihydrate, and glucose on the product obtained after the high-temperature reduction.
[0007] In some exemplary embodiments, the step of synthesizing the intermediate product titanium dioxide precursor further includes: dissolving a titanium source and acetic acid in ethanol and mixing them uniformly to form a first mixture; dissolving oxalic acid in a water-ethanol solution to obtain a second solution; adding the first mixture dropwise to the second solution and stirring to obtain a third mixture; and centrifuging and drying the precipitate in the third mixture to obtain the intermediate product titanium dioxide precursor.
[0008] In some exemplary embodiments, the titanium source is tetrabutyl titanate, and the first mixture is a homogeneous sol.
[0009] In some exemplary embodiments, the volume ratio of water to ethanol in the water-ethanol solution is 2:1, and the volume ratio of the first mixture to the second solution is 2:3.
[0010] In some exemplary embodiments, the stirring temperature in the stirring process is 50-60°C, and the stirring time is 2.5-3 hours.
[0011] In some exemplary embodiments, the drying temperature in the drying process is 60°C and the drying time is 12-24 hours.
[0012] In some exemplary embodiments, the step of reducing the titanium dioxide precursor with sodium borohydride at high temperature further includes: calcining and reducing the intermediate titanium dioxide precursor under an inert atmosphere to obtain a reduced product.
[0013] In some exemplary embodiments, the reduction temperature in the reduction process is 350°C and the reduction time is 1-3 hours.
[0014] In some exemplary embodiments, the step of obtaining heterostructured molybdenum disulfide / black titanium material by hydrothermal method using the product obtained after high-temperature reduction under the synergistic effect of thioacetamide, sodium molybdate dihydrate, and glucose further includes: taking an appropriate amount of the reduction product and continuously stirring it in a mixture of thioacetamide, sodium molybdate dihydrate, and glucose; and carrying out a hydrothermal reaction of the stirred mixture in a sealed container to obtain the heterostructured molybdenum disulfide / black titanium material.
[0015] In some exemplary embodiments, the mass ratio of thioacetamide, sodium molybdate dihydrate, and glucose in the mixture is 50:25:16, the stirring time in the stirring process is 20-90 min, the temperature of the hydrothermal reaction is 200-220℃, and the time of the hydrothermal reaction is 22-24 h.
[0016] In some exemplary embodiments, the step of obtaining heterostructured molybdenum disulfide / black titanium material by hydrothermal method from the product obtained after high-temperature reduction under the synergistic effect of sodium molybdate dihydrate thioacetamide and glucose further includes: centrifuging, washing and drying the precipitate obtained from the hydrothermal reaction to obtain the heterostructured molybdenum disulfide / black titanium material.
[0017] According to a second aspect of the present invention, a lithium-sulfur battery using a heterostructured molybdenum disulfide / black titanium material is provided, wherein the heterostructured molybdenum disulfide / black titanium material is prepared by the above-described method for preparing heterostructured molybdenum disulfide / black titanium material.
[0018] According to a third aspect of the present invention, there is a use of a heterostructured molybdenum disulfide / black titanium material, wherein the heterostructured molybdenum disulfide / black titanium material is prepared by the above-described method for preparing heterostructured molybdenum disulfide / black titanium material, and the heterostructured molybdenum disulfide / black titanium material is used in lithium-sulfur batteries.
[0019] In some exemplary embodiments, the heterostructured molybdenum disulfide / black titanium material is used as the cathode material of the lithium-sulfur battery.
[0020] According to the present invention, compared with the prior art, the superior effects are as follows: the method of obtaining black titanium by reduction using sodium borohydride is safe, simple, and inexpensive; simultaneously, due to the strong reducing effect of sodium borohydride, the molybdenum disulfide / black titanium material contains oxygen vacancies and low-valence titanium, introducing defect engineering, which can improve photocatalytic activity and resistance to photodegradation. Furthermore, the prepared molybdenum disulfide / black titanium material has a unique heterostructure, resulting in a valence band and conduction band closer to the charge / discharge voltage window of lithium-sulfur batteries and a narrower band gap, thus exhibiting better solar light absorption and photogenerated carrier separation capabilities, thereby greatly improving the specific capacity performance and cycle stability of light-gain lithium-sulfur batteries; at the same time, due to the presence of black titanium, the conductivity of this material is greatly improved and surpasses that of most current lithium-sulfur battery cathode materials. Attached Figure Description
[0021] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0022] Figure 1 A flowchart of the preparation method of the heterostructured molybdenum disulfide / black titanium material of the present invention is shown.
[0023] Figure 2 The XRD diffraction pattern of the heterostructured molybdenum disulfide / black titanium material prepared by the preparation method of the present invention is shown.
[0024] Figure 3 This is a scanning microscope image of the heterostructured molybdenum disulfide / black titanium material prepared by the preparation method of the present invention.
[0025] Figure 4 This is a transmission microscope image of black titanium material prepared by the method for preparing heterostructured molybdenum disulfide / black titanium material of the present invention.
[0026] Figure 5 This is a transmission microscope image of the heterostructured molybdenum disulfide / black titanium material prepared by the preparation method of the present invention.
[0027] Figure 6 This is a high-magnification transmission microscope image of the heterostructured molybdenum disulfide / black titanium material prepared by the preparation method of the present invention.
[0028] Figure 7 This is a SAED diagram of the heterostructured molybdenum disulfide / black titanium material prepared by the preparation method of the heterostructured molybdenum disulfide / black titanium material of the present invention.
[0029] Figure 8 The image shows the Ti 2p XPS spectrum of the heterostructured molybdenum disulfide / black titanium material prepared by the preparation method of the present invention.
[0030] Figure 9 The O1s XPS spectrum of the heterostructured molybdenum disulfide / black titanium material prepared by the preparation method of the heterostructured molybdenum disulfide / black titanium material of the present invention is shown.
[0031] Figure 10 This is a charge-discharge curve of a lithium-sulfur battery using the heterostructured molybdenum disulfide / black titanium material prepared by the above method.
[0032] Figure 11 This is a cycle performance diagram of a lithium-sulfur battery using the heterostructured molybdenum disulfide / black titanium material prepared by the above method according to the present invention. Detailed Implementation
[0033] The essence of the technical solutions in the embodiments of this application is explained in detail below.
[0034] In this embodiment, titanium dioxide precursor is synthesized from titanium source, acetic acid, oxalic acid and water and ethanol solvents. The titanium dioxide precursor is reduced by sodium borohydride at high temperature. The product obtained is then subjected to hydrothermal method under the synergistic effect of thioacetamide, sodium molybdate dihydrate and glucose to finally obtain heterostructured molybdenum disulfide / black titanium material.
[0035] The technical solutions of the embodiments of this application are described below with reference to specific examples, but the conditions and results described in the implementation do not constitute a limitation on the scope of protection of this application. In addition, the experimental methods described in the following embodiments are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0036] Figure 1 A schematic flowchart illustrating the preparation method of the heterostructured molybdenum disulfide / black titanium material of the present invention is shown. Figure 1 As shown, the preparation method of the heterostructured molybdenum disulfide / black titanium material of the present invention includes the following steps.
[0037] In step 101, the titanium source and acetic acid are dissolved in ethanol and mixed evenly to form mixture A.
[0038] In the embodiments of this application, the titanium source is tetrabutyl titanate, and the above mixture A is a homogeneous sol.
[0039] In step 102, oxalic acid is dissolved in a water-ethanol solution to obtain solution B.
[0040] In the embodiments of this application, the volume ratio of water to ethanol in the water-ethanol solution is 2:1.
[0041] In step 103, mixture A is added dropwise to solution B and stirred to obtain mixture C.
[0042] In the embodiments of this application, the volume ratio of mixture A to solution B is 2:3, the stirring temperature during the stirring process is 50-60℃, preferably 55℃, and the stirring time is 2.5-3h, preferably 3h.
[0043] In step 104, the precipitate in mixture C is centrifuged and dried to obtain the intermediate product titanium dioxide precursor.
[0044] In the embodiments of this application, the drying temperature in the drying process is 60°C, and the drying time is 12-24 hours, preferably 12 hours.
[0045] In step 105, the intermediate product titanium dioxide precursor is subjected to calcination reduction treatment under an inert atmosphere to obtain a reduced product.
[0046] In this embodiment of the application, the reduction temperature in the reduction process is 350°C, and the reduction time is 1-3 hours, preferably 2 hours.
[0047] In step 106, an appropriate amount of the reduction product is continuously stirred in a mixture of thioacetamide, sodium molybdate dihydrate, and glucose.
[0048] In the embodiments of this application, the mass ratio of thioacetamide, sodium molybdate dihydrate, and glucose in the mixture is 50:25:16, and the stirring time in the stirring process is 20-90 min, preferably 60 min.
[0049] In step 107, the above-mentioned mixture after stirring is subjected to a hydrothermal reaction in a sealed container to obtain a heterostructured molybdenum disulfide / black titanium material. Specifically, the precipitate obtained from the hydrothermal reaction is centrifuged, washed, and dried to obtain the heterostructured molybdenum disulfide / black titanium material.
[0050] In this embodiment, the temperature of the hydrothermal reaction is 200-220℃, preferably 220℃; the time of the hydrothermal reaction is 22-24h, preferably 24h.
[0051] The inventors conducted the following verifications regarding the products prepared by the above methods and steps.
[0052] Figure 2 The above method produces the XRD diffraction pattern of the heterostructured molybdenum disulfide / black titanium material. Figure 3 These are scanning microscope images of the heterostructured molybdenum disulfide / black titanium material prepared by the above method. Figure 4 These are transmission microscope images of the black titanium material prepared by the above method. Figure 5 This is a transmission microscope image of the heterostructured molybdenum disulfide / black titanium material prepared by the above method. Figure 6 This is a high-magnification transmission microscope image of the heterostructured molybdenum disulfide / black titanium material prepared by the above method. Figure 7 This is the SAED image of the heterostructured molybdenum disulfide / black titanium material prepared by the above method.
[0053] like Figure 2 As shown, the product prepared by the above method was identified by X-ray powder diffraction as molybdenum disulfide / black titanium material. The microstructure of this molybdenum disulfide / black titanium material is shown in the figure below. Figure 3As shown, the molybdenum disulfide / black titanium material exhibits a morphology of tightly connected particles of different sizes, such as... Figure 4 , 5 As shown, the transmission electron microscope (TEM) image demonstrates the successful synthesis of the heterostructure of molybdenum disulfide / black titanium material. Further high-resolution transmission electron microscopy (HRTEM) characterization of the prepared product is shown in the image. Figure 6 As shown, the lattice fringes of molybdenum disulfide and black titanium are clearly visible. Measurements show that the lattice fringes spacing of molybdenum disulfide is 0.616 nm, corresponding to the (002) crystal plane; the lattice fringes spacing of black titanium is 0.352 nm, corresponding to the (101) crystal plane. Meanwhile, as shown... Figure 7 As shown, the selected area electron diffraction pattern reveals that the material has a polycrystalline structure. All of the above results prove that the molybdenum disulfide / black titanium heterostructure was successfully synthesized.
[0054] The heterostructured molybdenum disulfide / black titanium material prepared by the above method was further characterized by X-ray photoelectron spectroscopy. Figure 8 This is the Ti 2p XPS spectrum of the heterostructured molybdenum disulfide / black titanium material. From the spectrum, it can be seen that the synthesized molybdenum disulfide / black titanium material contains elements other than Ti. 4+ Ti outside 3+ . Figure 9 The image shows the O1s XPS spectrum of the heterostructured molybdenum disulfide / black titanium material. The image shows the signal peak of oxygen vacancies in the synthesized molybdenum disulfide / black titanium material. All of the above results indicate that the titanium dioxide precursor was successfully reduced by sodium borohydride.
[0055] According to this embodiment, compared with the prior art, the superior effects are as follows: the method of obtaining black titanium by reduction using sodium borohydride is safe, simple and low cost; at the same time, due to the strong reducing effect of sodium borohydride, the molybdenum disulfide / black titanium material has oxygen vacancies and low-valence titanium, which introduces defect engineering and can improve photocatalytic activity and photodegradation resistance.
[0056] This application also describes a heterostructured molybdenum disulfide / black titanium material prepared by the above-described method for preparing heterostructured molybdenum disulfide / black titanium material.
[0057] According to this embodiment, the molybdenum disulfide / black titanium material prepared by the above preparation method has a unique heterostructure, thus having a valence band and conduction band closer to the charge and discharge voltage window of the lithium-sulfur battery and a narrower band gap, resulting in better solar light absorption and photogenerated carrier separation capabilities; at the same time, due to the presence of black titanium, the conductivity of this material is greatly improved and is superior to most current lithium-sulfur battery cathode materials.
[0058] This application also describes an application of the above-mentioned heterostructured molybdenum disulfide / black titanium material, which is prepared by the above-mentioned method for preparing heterostructured molybdenum disulfide / black titanium material, and is used in lithium-sulfur batteries.
[0059] In the embodiments of this application, the above-mentioned heterostructured molybdenum disulfide / black titanium material is used as the positive electrode material of lithium-sulfur batteries.
[0060] According to this embodiment, since the heterostructured molybdenum disulfide / black titanium material prepared by the above preparation method has abundant oxygen vacancies and low-valence titanium, applying this material to the cathode of a lithium-sulfur battery can improve photocatalytic activity and resistance to photodegradation, increase the separation rate of photogenerated holes and photogenerated electrons, and thus improve the utilization rate of sunlight. This effectively improves a series of electrochemical properties of the light-gain lithium-sulfur battery, and further greatly improves the specific capacity performance and cycle stability of the light-gain lithium-sulfur battery.
[0061] Figure 10 The present invention provides a charge-discharge curve of a lithium-sulfur battery using the heterostructure molybdenum disulfide / black titanium material prepared by the above method. It can be seen that at a current density of 0.5C, the molybdenum disulfide / black titanium cathode exhibits a discharge specific capacity of over 1600 mAh g⁻¹ under illumination conditions, which is about 20% higher than the discharge specific capacity under no-light conditions, indicating that it has excellent high specific capacity performance. Figure 11 The graph shows the cycle performance of a lithium-sulfur battery using the heterostructured molybdenum disulfide / black titanium material prepared by the above method. It can be seen that the molybdenum disulfide / black titanium cathode exhibits excellent cycle stability, with its reversible capacity remaining above 1000 mAh g⁻¹ after approximately 40 cycles, significantly better than batteries under no-light conditions. This demonstrates that this heterostructured molybdenum disulfide / black titanium material possesses excellent electrochemical performance.
[0062] It should be understood that the phrase "an embodiment" or "one embodiment" throughout the specification means that a specific feature, structure, or characteristic related to the embodiment is included in at least one embodiment of this application. Therefore, "in one embodiment" or "in an embodiment" appearing throughout the specification do not necessarily refer to the same embodiment. Furthermore, these specific features, structures, or characteristics can be combined in any suitable manner in one or more embodiments. It should be understood that in the various embodiments of this application, the sequence numbers of the above-described processes do not imply a sequential order of execution; the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of this application. The sequence numbers of the above-described embodiments are merely descriptive and do not represent the superiority or inferiority of the embodiments.
[0063] It should be noted that, in this document, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Unless otherwise specified, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes that element.
[0064] The above description is merely an embodiment of this application, but the scope of protection of this application is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application should be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of the claims.
Claims
1. The application of a heterostructured molybdenum disulfide / black titanium material in a photo-gain lithium-sulfur battery, characterized in that, Methods for preparing heterostructured molybdenum disulfide / black titanium materials include: Titanium dioxide precursor was synthesized using titanium source, acetic acid, oxalic acid, and water and ethanol solvents as raw materials. The titanium dioxide precursor was reduced at high temperature with sodium borohydride; and The product obtained after high-temperature reduction was subjected to hydrothermal treatment with thioacetamide, sodium molybdate dihydrate and glucose to obtain a heterostructured molybdenum disulfide / black titanium material. The step of reducing the titanium dioxide precursor with sodium borohydride at high temperature further includes: The intermediate titanium dioxide precursor is subjected to calcination and reduction treatment under an inert atmosphere to obtain a reduced product; the reduction temperature in the reduction treatment is 350℃, and the reduction time is 1-3h; the step of obtaining heterostructured molybdenum disulfide / black titanium material by hydrothermal method under the synergistic effect of thioacetamide, sodium molybdate dihydrate, and glucose after high-temperature reduction further includes: A suitable amount of the reduction product was continuously stirred in a mixture of thioacetamide, sodium molybdate dihydrate, and glucose; and The mixture after stirring was subjected to a hydrothermal reaction in a sealed container to obtain the heterostructured molybdenum disulfide / black titanium material. The mass ratio of thioacetamide, sodium molybdate dihydrate, and glucose in the mixture is 50:25:16, and the stirring time in the stirring process is 20-90 minutes. The hydrothermal reaction is carried out at a temperature of 200-220℃ for 22-24 hours.
2. The preparation method according to claim 1, characterized in that, The step of synthesizing the intermediate product titanium dioxide precursor further includes: The titanium source and acetic acid are dissolved in ethanol and mixed evenly to form a first mixture; Oxalic acid was dissolved in an aqueous-ethanol solution to obtain a second solution; The first mixture is added dropwise to the second solution and stirred to obtain a third mixture; and The precipitate in the third mixture is centrifuged and dried to obtain the intermediate product, titanium dioxide precursor.
3. The preparation method according to claim 2, characterized in that, The titanium source is tetrabutyl titanate, and the first mixture is a homogeneous sol. The volume ratio of water to ethanol in the water-ethanol solution is 2:1, and the volume ratio of the first mixture to the second solution is 2:
3.
4. The preparation method according to claim 2, characterized in that, The stirring temperature during the stirring process is 50-60℃, and the stirring time is 2.5-3h. The drying temperature in the drying process is 60℃, and the drying time is 12-24h.
5. The preparation method according to claim 1, characterized in that, The step of obtaining heterostructured molybdenum disulfide / black titanium material by hydrothermal method from the product obtained after high-temperature reduction under the synergistic effect of thioacetamide, sodium molybdate dihydrate, and glucose further includes: The precipitate obtained from the hydrothermal reaction is centrifuged, washed, and dried to obtain the heterostructured molybdenum disulfide / black titanium material.
Citation Information
Patent Citations
MOS2 (molybdenum disulfide) and TiO2 (titanium dioxide) nanocomposites and production method thereof
CN103426648A
Preparation method of titanium dioxide-modified MoS2 lithium ion battery negative electrode material
CN110323424A